CCR7 Maintains Nonresolving Lymph Node and Adipose Inflammation in Obesity - Hellmann, Jason (Diabetes, 2016)
Accumulation of immune cells in adipose tissue promotes insulin resistance in obesity. Although innate and adaptive immune cells contribute to adipose inflammation, the processes that sustain these interactions are incompletely understood. Here we show that obesity promotes the accumulation of CD11c(+) adipose tissue immune cells that express C-C chemokine receptor 7 (CCR7) in mice and humans, and that CCR7 contributes to chronic inflammation and insulin resistance. We identified that CCR7(+) macrophages and dendritic cells accumulate in adipose tissue in close proximity to lymph nodes (LNs) (i.e., perinodal) and visceral adipose. Consistent with the role of CCR7 in regulating the migration of immune cells to LNs, obesity promoted the accumulation of CD11c(+) cells in LNs, which was prevented by global or hematopoietic deficiency of Ccr7. Obese Ccr7(−/−) mice had reduced accumulation of CD8(+) T cells, B cells, and macrophages in adipose tissue, which was associated with reduced inflammatory signaling. This reduction in maladaptive inflammation translated to increased insulin signaling and improved glucose tolerance in obesity. Therapeutic administration of an anti-CCR7 antibody phenocopied the effects of genetic Ccr7 deficiency in mice with established obesity. These results suggest that CCR7 plays a causal role in maintaining innate and adaptive immunity in obesity.